2020
DOI: 10.1021/acsanm.9b01786
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Phosphorus Quantum Dots for Cell Imaging

Abstract: Fibrous phosphorus is a crystalline structure belonging to the extensive family of phosphorus allotropes. The material’s structure consists of 1D tubular layers held together by van der Waals forces and is a semiconductor with an optical band gap of 2.1 eV in its bulk form. With these properties in mind, we developed a facile solution-based method for the fabrication of fibrous phosphorus quantum dots (FPQDs). The FPQDs were prepared by sonicating the material in N-methylpyrrolidone and centrifuging to separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 63 publications
(96 reference statements)
2
21
0
Order By: Relevance
“…The band gaps were calculated to be 2.7, 2.53, and 2.5 eV with the centrifugal speeds of 10 000, 8000, and 6000 rpm, respectively. They agree with the results observed for FPQDs and bulk samples . For instance, FPQDs with an average size of 3.8 nm have a band gap of 3.3 eV, whereas the optical band gap observed for bulk FP is 2.1 eV.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The band gaps were calculated to be 2.7, 2.53, and 2.5 eV with the centrifugal speeds of 10 000, 8000, and 6000 rpm, respectively. They agree with the results observed for FPQDs and bulk samples . For instance, FPQDs with an average size of 3.8 nm have a band gap of 3.3 eV, whereas the optical band gap observed for bulk FP is 2.1 eV.…”
Section: Resultssupporting
confidence: 90%
“…In addition, phosphorus is one of the most important elements in living organisms and so FP has a huge advantage in cell imaging. Amaral et al found that FP quantum dots (FPQDs) can produce a blue fluorescence in human adenocarcinoma cells . The quantum confinement effect leads to broadening the band gap, resulting in the emission of a blue fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…XPS measurements (Supplementary Fig. 1 ) show two peaks with binding energies of ~130.6 and 131.2 eV, which correspond to 2 p 3/2 and 2 p 1/2 of phosphorus–phosphorus bonds in 1D vdW FRP, respectively 5 , 39 . The EDS spectrum (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is composed of tubular strands with a monoclinic crystal structure 28 . Fibrous phosphorus also belongs to the family of phosphorus allotropes, composed of 1D tubular layers held together by van der Waals interactions 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%